Conduction mechanism, impedance spectroscopic investigation and dielectric behavior of La0.5Ca0.5−xAgxMnO3 manganites with compositions below the concentration limit of silver solubility in perovskites (0 ≤ x ≤ 0.2). Issue 22 (14th June 2015) - Rahmouni, H.; Smari, M.; Cherif, B.; Dhahri, E.; Khirouni, K.
<x xml:space="preserve">Abstract</x> This study presents the electrical properties, complex impedance analysis and dielectrical behavior of La0.5Ca0.5−xAgxMnO3 manganites.